Non-Spherical Polymeric Nanoparticles : Synthesis and Applications - Sri Agustina; Hadi Wahyudi; Marta Pramudita; Alia Badra Pitaloka (Universitas Muhammadiyah Purwokerto, 2025)
Non-spherical polymeric nanoparticles have emerged as a promising functional materials due to their distinctive physicochemical properties and enhanced performance in various applications. The morphologies of nanoparticles play a critical role in determining their biological and chemical behavior, especially in targeted delivery and interaction with complex environments. Advances in synthesis techniques now allow precise control over particle morphology, enabling the production of polymeric nanoparticles in various morphologies such as rods, discs, and ellipsoids. This review highlights recent developments in the synthesis methods of non-spherical polymeric nanoparticles and explores their expanding range of applications, with a focus on their potential as nanocarriers in biomedical, agricultural, and industrial fields.